Effects of Kaolin Surface Treatments on the Thermomechanical Properties and on the Degradation of Polypropylene - Melia Guessoum; Sorya Nekkaa; Françoise Fenouillot-Rimlinger; Nacerddine Haddaoui (International Journal of Polymer Science)
The effects of kaolin content and treatments on the thermal and mechanical properties and on the degradation of polypropylene were examined using mechanical tests, differential scanning calorimetry (DSC), and thermogravimetry (TGA). The weak interactions filler/matrix have been reinforced using a modification with urea then with an ammonium salt and a surface treatment with a silane coupling agent. The XRD results showed that the peak at the d-value of 10.7 Å increases in urea/kaolin complex, but the treatment with the ammonium salt caused the return to the initial state of the clay. FTIR results showed the appearance of new bands characteristic of the interactions between urea and kaolinite and the alkylammonium and kaolinite. The mechanical properties of the composites exhibited important variations while the DSC results showed the decrease of the crystallization temperature as a function of kaolin content. TGA thermograms pointed out the improvement of the composites' thermal stability.